Correlations of oral behaviors, pain, and psychological distress among patients with temporomandibular disorders: clinical investigation of axial II evaluation - Yu, Yan; Wang, Lili; Chen, Chunxia; Wang, Mengmeng; Nie, Shuai; Fu, Lin (Frontiers in Public Health, 2025)
PurposeThis cross-sectional, observational study assessed physical, psychological and behavioral factors related to patients with temporomandibular disorder (TMD) using Axis II assessment instruments with diagnostic criteria for TMD (DC/TMD) and investigated the correlations among oral behavior, pain, and psychological distress in patients with temporomandibular disorders.MethodsParticipants were recruited from the Department of TMD at the authors’ hospital. The TMD group comprised 96 patients (27 males and 69 females; mean age 39.10 ± 10.83 years), stratified into three clinical subgroups based on primary symptoms: myofascial pain dysfunction syndrome (MPDS; subgroup 1), internal derangement (subgroup 2), and osteoarthritis (subgroup 3). The control group consisted of 111 individuals (42 males and 69 females; mean age 35.05 ± 7.94 years) with no history of TMD. Demographic information, oral behaviors, pain, and psychological outcomes of the TMD group were assessed using self-report questionnaires according to the diagnostic criteria of axial II. The non-TMD group was evaluated using similar instruments except for pain and jaw functional limitations.ResultsCompared with the non-TMD group, the TMD group presented significantly greater levels of unhealthy oral behaviors and psychological outcomes, including anxiety, depression, and somatic symptoms. Within the TMD group, participants diagnosed with MPDS were found to have more psychological symptoms than those diagnosed with internal derangement and osteoarthritis. The psychological outcomes of patients with TMD were shown to be significantly positively correlated with their pain status and oral behaviors (rs = 0.23 ~ 0.52). The indirect effect of chronic pain was found to be significant in the relationships between oral behaviors and psychological outcomes, including anxiety, depression, and somatic symptoms.ConclusionOral behaviors and chronic pain were closely associated with psychosocial distress among patients with TMD. The effect of oral behavior on psychological distress is exerted indirectly through chronic pain. This study contributes to the conceptual framework for the development of individualized diagnostic and therapeutic strategies for patients with TMD.